Informe de la vigilancia y control poblacional de larvas de Aedes aegypti, Linnaeus, 1762 (diptera culicidea) en el distrito de Belén - provincia de Maynas - departamento de Loreto - Perú, periodo 2011-2014 - Solignac Barbarán, Llesy Cleyri (2019)
Dengue is an arboviral disease transmitted by the bite of the Aedes aegypti mosquito. In order to evaluate the surveillance and population control activities of Aedes aegypti in the district of Belén-Maynas Province, Department of Loreto, during the period 2011-2014. Held at the “6 de Octubre” health center located in Prolongación Yurimaguas No. 276. 06 sectors were evaluated, the average number of homes inspected by each health inspector was 20 homes / day. The surveillance and vector control format was used for the inspection of homes used by the Ministry of Health. In addition, post-control entomological surveillance was carried out to determine the impact of vector control, which were expressed in a post-control aedic index. The results of the AI are similar during the years 2011, 2013 and 2014 (p> 0.05), presenting an annual average of 6.00 ± 5.20 (median ± interquartile range); of the IB is similar during the years 2011, 2013 and 2014, presenting an annual average of 7.30 ± 6.05 (median ± interquartile range). In surveillance, the results of the IRs are similar during the years 2011, 2013 and 2014 (p > 0.05), presenting an annual average of 0.80 ± 0.53 (median ± interquartile range). The three entomological indices (IA, IB and IR) demonstrated the constant generation of Aedes aegypti breeding sites in homes, which could reflect a weakness in the detection and control of vector breeding sites in the home, as well as a rapid replacement of them. by the human population.